ANALISIS PENDAPATAN DAN EFISIENSI USAHA PEMBESARAN IKAN NILA (Oreochromis Niloticus) DI DESA MEKAR MULYA KECAMATAN PENARIK KABUPATEN MUKOMUKO - Irwandi, Irwandi; Badrudin, Redy; Suryanty, Melly (Jurnal AGRISEP, 2015)
This research aims to understand the Income and the Efficiency of tilapia farming ( Oreochromis niloticus ) in Desa Mekar Mulya Kecamatan Penarik Kabupaten Mukomuko. Respondents in this research is determinated by using the method the census. Respondents taken is 24 farmers enlargement tilapia. The collection of data used data on primary and secondary data. The analysis method uses profitability and R / C ratio. The result showed large operating income enlargement tilapia in the village of Mekar Mulya Subdistrict Penarik District Mukomuko get the average income received by farmers tilapia as much as Rp.9.652.038,62 per season stocking or Rp.48.535,38 per square meters. Eatimated R / C ratio i s 1,25 meaning that the actual enlargement of the tilapia of in the village of Mekar Mulya Subdistrict Penarik District Mukomuko is Profitable and efficient.